2018
DOI: 10.1172/jci96817
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal P-glycoprotein exports endocannabinoids to prevent inflammation and maintain homeostasis

Abstract: Neutrophil influx into the intestinal lumen is a critical response to infectious agents, but is also associated with severe intestinal damage observed in idiopathic inflammatory bowel disease. The chemoattractant hepoxilin A3, an eicosanoid secreted from intestinal epithelial cells by the apically restricted efflux pump multidrug resistance protein 2 (MRP2), mediates this neutrophil influx. Information about a possible counterbalance pathway that could signal the lack of or resolution of an apical inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 55 publications
(74 reference statements)
0
56
0
Order By: Relevance
“…To support the biofilm data and our previous induced HT-29 adherence observations (30, 31), we performed adherence analysis on a human intestinal organoid-derived epithelial monolayer (HIODEM) model. The model is derived from stem cells isolated from intestinal tissue, propagated as organoids, and subsequently trypsinized and seeded onto transwells to generate a two-dimensional (2-D) polarized, differentiated model of the intestinal epithelium in which enterocytes, mucus-producing goblet cells, and antigen sampling M cells are present (3438). With the model derived from the ascending colon, S. flexneri 2457T subcultured in IVLCs displayed putative adherence factors contacting the epithelial cells (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…To support the biofilm data and our previous induced HT-29 adherence observations (30, 31), we performed adherence analysis on a human intestinal organoid-derived epithelial monolayer (HIODEM) model. The model is derived from stem cells isolated from intestinal tissue, propagated as organoids, and subsequently trypsinized and seeded onto transwells to generate a two-dimensional (2-D) polarized, differentiated model of the intestinal epithelium in which enterocytes, mucus-producing goblet cells, and antigen sampling M cells are present (3438). With the model derived from the ascending colon, S. flexneri 2457T subcultured in IVLCs displayed putative adherence factors contacting the epithelial cells (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many studies have focused on the research of the ECS and its implication on immune and inflammatory diseases, including periodontal disease . ‒ Most of these studies have approached this issue through cells cultures such as human gingival fibroblasts and ligament periodontal cells .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have focused on the research of the ECS and its implication on immune and inflammatory diseases, including periodontal disease. [31][32][33] Most of these studies have approached this issue through cells cultures such as human gingival fibroblasts and ligament periodontal cells. 34 However, our research group reported anti-inflammatory effects on gingival tissue and osteoprotective effects on alveolar bone induced by both a CB2r and a CB1r agonist (HU308 and meth-AEA, respectively), in a model of LPS-induced periodontal disease in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that the transporter P-glycoprotein (P-gp) secretes endocannabinoids into the intestinal lumen that counteract the pro-inflammatory actions of the neutrophil chemoattractant eicosanoid hepoxilin A3. Moreover, the anti-inflammatory actions of P-gp—secreted endocannabinoids—are mediated by CB2 receptors on neutrophils [ 34 ]. Kapellos et al recently published that the CB2 deficiency exacerbates acute neutrophils mobilization to sites of inflammation [ 35 ].…”
Section: The Roles Of the Endocannabinoid System In Immunitymentioning
confidence: 99%